2003
DOI: 10.1046/j.1365-3016.2003.00519.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood malnutrition and its predictors in rural Malawi

Abstract: We prospectively followed up a population-based cohort of 767 rural Malawian children from birth to 36 months to characterise the timing and predictors of malnutrition. Underweight and wasting incidence peaked between 6 and 18 months of age, whereas stunting incidence was highest during the first 6 months of age. After infancy about 40% of the children were underweight, 70% stunted, and about 4% wasted. Small size during the first 3 months of life predicted the incidence of severe underweight (relative risk [9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 14 publications
9
78
1
Order By: Relevance
“…A study of 767 rural Malawian children up to 36 months of age (Maleta et al 2003) found that one of the predictors of severe underweight was residence far away from a health facility, but did not observe a reason for this. However, it is suggested that malnutrition could be alleviated by increased accessibility to interventions relating to feeding patterns; people living in more remote areas may benefit the most from such interventions.…”
Section: Spatial Effectsmentioning
confidence: 96%
“…A study of 767 rural Malawian children up to 36 months of age (Maleta et al 2003) found that one of the predictors of severe underweight was residence far away from a health facility, but did not observe a reason for this. However, it is suggested that malnutrition could be alleviated by increased accessibility to interventions relating to feeding patterns; people living in more remote areas may benefit the most from such interventions.…”
Section: Spatial Effectsmentioning
confidence: 96%
“…Stunting, which primarily affects children in their second year of life (2)(3)(4) , is a result of chronic inadequate intake of energy and nutrients, as well as frequent infections (1) .…”
mentioning
confidence: 99%
“…In Nigeria, Olusanya et al [37], in a cross-sectional survey to assess the impact of IUGR on growth at one week of life, showed an association between IUGR and nutritional disturbances, results confirmed later in this same cohort at the age of 3 months [38]. Comparable results on various anthropometric indices have been described in Kenya [39], Ethiopia [40] and Malawi [41].…”
Section: Discussionmentioning
confidence: 82%